2020
DOI: 10.1111/dmcn.14671
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive improvement after cochlear implantation in deaf children with associated disabilities

Abstract: AIM To monitor functional auditory and non-verbal cognitive skills in children with cochlear implants who had associated disabilities over a 24-month period and define how cochlear implantation may impact on non-verbal cognition by restoring functional auditory skills. METHOD Sixty-four children with cochlear implants (36 females, 28 males; mean age 4y 3mo, SD 3y 5mo, 9mo-14y 5mo) were recruited and divided into three groups: children with typical development group (TDG); children with associated disabilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…In reference to the degree of response in the auditory and language domains, three levels of beneficial effects can be derived from class 1 and 2 studies: (A) the vast majority of children (approximately 80-90%) achieved greater environmental sound awareness, leading to improved adaptive skills; (B) approximately half of the children appeared to improve in speech awareness and in receptive language; (C) a smaller minority developed some form of expressive language, which occasionally became the primary communication mode, but more often improved communication by conjoining sign language or other forms of augmentative alternative communication (Tables 2 and 3). While these response rates are clearly below the achievements of children without additional disabilities, it is particularly noticeable that even children who do not develop expressive language usually improve in adaptive behaviors [16] and/or in environmental sound awareness [22,24]. In reference to the timing of the responses, children with additional disabilities often displayed a slower rate of improvement, possibly reaching the maximum response level 2-3 years after CI, as compared to control children reaching higher response levels at 12 months [16,29,37].…”
Section: Resultsmentioning
confidence: 94%
“…In reference to the degree of response in the auditory and language domains, three levels of beneficial effects can be derived from class 1 and 2 studies: (A) the vast majority of children (approximately 80-90%) achieved greater environmental sound awareness, leading to improved adaptive skills; (B) approximately half of the children appeared to improve in speech awareness and in receptive language; (C) a smaller minority developed some form of expressive language, which occasionally became the primary communication mode, but more often improved communication by conjoining sign language or other forms of augmentative alternative communication (Tables 2 and 3). While these response rates are clearly below the achievements of children without additional disabilities, it is particularly noticeable that even children who do not develop expressive language usually improve in adaptive behaviors [16] and/or in environmental sound awareness [22,24]. In reference to the timing of the responses, children with additional disabilities often displayed a slower rate of improvement, possibly reaching the maximum response level 2-3 years after CI, as compared to control children reaching higher response levels at 12 months [16,29,37].…”
Section: Resultsmentioning
confidence: 94%
“…Micheletti et al 2 explored how nonverbal cognitive skills change over time among 64 children who received cochlear implants, and how functional auditory skills post‐cochlear implant may influence nonverbal cognitive functions. The authors compared children with disabilities to typically developing children.…”
mentioning
confidence: 99%
“…This study raises an intriguing recognition of improvement in nonverbal cognitive abilities for children with intellectual disabilities who receive implants. Micheletti et al 2 reported that the children with associated disabilities linked to non‐verbal cognitive disorders group (ADG2) were on average slightly younger at the time of their implant compared to the other two groups. Children whose developmental or cognitive assessments occur after 2 years of age tend to display more stability of nonverbal cognitive performance compared to children who are evaluated as infants or toddlers.…”
mentioning
confidence: 99%